Attempted salvage of infected cardiovascular implantable electronic devices: Are there clinical factors that predict success?. Issue 5 (3rd April 2018) - Peacock, James E.; Stafford, Jeanette M.; Le, Katherine; Sohail, Muhammad Rizwan; Baddour, Larry M.; Prutkin, Jordan M.; Danik, Stephan B.; Vikram, Holenarasipur R.; Hernandez‐Meneses, Marta; Miró, José M.; Blank, Elisabeth; Naber, Christoph K.; et al.
Abstract: Background: Published guidelines mandate complete device removal in cases of cardiovascular implantable electronic device (CIED) infection. Clinical predictors of successful salvage of infected CIEDs have not been defined. Methods: Data from the Multicenter Electrophysiologic Device Infection Collaboration, a prospective, observational, multinational cohort study of CIED infection, were used to investigate whether clinical predictors of successful salvage of infected devices could be identified. Results: Of 433 adult patients with CIED infections, 306 (71%) underwent immediate device explantation. Medical management with device retention and antimicrobial therapy was initially attempted in 127 patients (29%). "Early failure" of attempted salvage occurred in 74 patients (58%) who subsequently underwent device explantation during the index hospitalization. The remaining 53 patients (42%) in the attempted salvage group retained their CIED. Twenty‐six (49%) had resolution of CIED infection (successful salvage group) whereas 27 patients (51%) experienced "late" salvage failure. Upon comparing the salvage failure group, early and late (N = 101), to the group experiencing successful salvage of an infected CIED (N = 26), no clinical or laboratory predictors of successful salvage were identified. However, by univariate analysis, coagulase‐negative staphylococci as infecting pathogens (P = 0.0439) and the presence of a lead vegetation (P = 0.024) were associated with overall failed salvage. Conclusions: In patients with definite CIED infections, clinical and laboratory variables cannot predict successful device salvage. Until new data are forthcoming, device explantation should remain a mandatory and early management intervention in patients with CIED infection in keeping with existing expert guidelines unless medical contraindications exist or patients refuse device removal.